Formation of the digestive system in zebrafish. I. Liver morphogenesis - Field, Holly A.; Ober, Elke A.; Roeser, Tobias; Stainier, Didier Y. R. (Developmental Biology, 2003)
Despite the essential functions of the digestive system, much remains to be learned about the cellular and molecular mechanisms responsible for digestive organ morphogenesis and patterning. We introduce a novel zebrafish transgenic line, the gutGFP line, that expresses GFP throughout the digestive system, and use this tool to analyze the development of the liver. Our studies reveal two phases of liver morphogenesis: budding and growth. The budding period, which can be further subdivided into three stages, starts when hepatocytes first aggregate, shortly after 24 h postfertilization (hpf), and ends with the formation of a hepatic duct at 50 hpf. The growth phase immediately follows and is responsible for a dramatic alteration of liver size and shape. We also analyze gene expression in the developing liver and find a correlation between the expression of certain transcription factor genes and the morphologically defined stages of liver budding. To further expand our understanding of budding morphogenesis, we use loss-of-function analyses to investigate factors potentially involved in this process. It had been reported that no tail mutant embryos appear to lack a liver primordium, as assessed by gata6 expression. However, analysis of gutGFP embryos lacking Ntl show that the liver is in fact present. We also find that, in these embryos, the direction of liver budding does not correlate with the direction of intestinal looping, indicating that the left/right behavior of these tissues can be uncoupled. In addition, we use the cloche mutation to analyze the role of endothelial cells in liver morphogenesis, and find that in zebrafish, unlike what has been reported in mouse, endothelial cells do not appear to be necessary for the budding of this organ. © 2003 Elsevier Science (USA). All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Chirality; cloche; Endoderm; Hepatocytes